2020
DOI: 10.1007/s11664-020-07991-5
|View full text |Cite
|
Sign up to set email alerts
|

The High Potential for Waste Heat Recovery in Hybrid Vehicles: A Comparison Between the Potential in Conventional and Hybrid Powertrains

Abstract: In future mobility, the mix of different drive trains will probably be much more diverse than it is today. According to a large number of scenario analyses, a predominant number of vehicles will continue to be based on the internal combustion engine (ICE), while an increasing number of hybrid vehicles are expected. To achieve the required reductions in CO2 emissions it is necessary to investigate all potential technologies for efficiency improvement. Therefore in this work the potential of waste heat recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Due to the lower ICE wall heat flows in the hybrid vehicle, as also described in Ref. 16, there are less heat flows into the cooling system. Therefore, the recovery of heat from the exhaust gas has a higher effect for shortening the warm-up phase.…”
Section: Results Achieved For the Two Reference Vehiclesmentioning
confidence: 94%
See 2 more Smart Citations
“…Due to the lower ICE wall heat flows in the hybrid vehicle, as also described in Ref. 16, there are less heat flows into the cooling system. Therefore, the recovery of heat from the exhaust gas has a higher effect for shortening the warm-up phase.…”
Section: Results Achieved For the Two Reference Vehiclesmentioning
confidence: 94%
“…Reference vehicles at the roller dynamometer test bench. 16 of this exhaust gas is even higher than in the conventional vehicles. In addition, the comparison points that waste heat and exergy in the exhaust gas are higher in hybrid vehicles, despite the fact that the ICE has a higher efficiency.…”
Section: Production Of Tem (Industrial)mentioning
confidence: 82%
See 1 more Smart Citation
“…Kober et al [12] used the World Light Vehicle Test Program (WLTP) cycle, finding that hybrid vehicles have the greatest potential for waste heat recovery. Kober M. [13] demonstrated that the higher the efficiency of the internal combustion engine, the higher the energy in the exhaust gas of the Hybrid Electrical Vehicles (HEVs), and the higher the efficiency of power generation. Ezzitouni S. et al [14] proposed a model to predict the power generation efficiency of automotive thermoelectric generators at different operating points.…”
Section: Introductionmentioning
confidence: 99%
“…Direct heat recovery seems a technology more easily to be implemented, with similar benefits [18,19]. Also the coolant energy can be exploited for low grade thermal recovery [20,21] and this integration can have additional benefits also in electrified powertrains and hybrid vehicles [22,23]. Other opportunities to integrated thermal management are referred to the cooling of the intake air of the engine, by means of water charge air cooler or chiller-based system, in order to increase engine volumetric efficiency [24,25].…”
Section: Introductionmentioning
confidence: 99%